Computer vision, pattern recognition, image processing, and graphics : 6th National Conference, NCVPRIPG 2017, Mandi, India, December 16-19, 2017, Revised selected papers /: 6th National Conference, NCVPRIPG 2017, Mandi, India, December 16-19, 2017, Revised selected papers. (2018) - Unknown
No abstract available